Метал браслетів Херсонеса - Ольговський, С.Я. (Археологія, 2001)
Висвітлено результати спектроаналітичного дослідження бронзових браслетів пізньоантичного Херсонеса. Виділено металургійні групи металу. Автор доходить висновку щодо уніфікації сплавів у перших століттях н.е. і неможливість виділення хімічних груп та ототожнення їх з рудними родовищами. В статье рассматриваются бронзовые браслеты позднеантичного Херсонеса (I—IV вв. н. э.). Кроме типологической характеристики представлены результаты спектрального анализа браслетов из собрания Фондов Херсонесского историко-археологического заповедника. На основании статистической обработки результатов спектрального анализа выделены металлургические группы металла. Какой-либо зависимости рецепта сплава от типа изделия не установлено. В целом в первые века н. э. происходила унификация сплавов, что и подтвердили настоящие анализы, хотя в то время стали использовать новую легирующую примесь — цинк, который в различном сочетании с традиционными примесями — оловом и свинцом — образует группу многокомпонентных сплавов и латуней. Использование комплексных лигатур не позволяет выделить химические труппы металла и привязать их к конкретным рудным источникам. The paper considers bronze bracelets from the Later Ancient Chersonese (I–IV centuries AD). Besides a typological characteristic, the results of spectral analysis of the bracelets from the collection of die Chersonese historical-archaeological reserve funds are presented. Based on the statistical treatment of the results of spectral analysis, the metallurgical groups of the metal are separated, and no dependence of the alloy composition on the type of article is found. On the whole, a unification of alloys proceeded for the first centuries AD, which is confirmed by these analyses. At the same time, a new alloying admixture, zinc, came into use in various combinations with the traditional admixtures, tin, and lead, which led to the appearance of the group of multicomponent alloys and brasses. The use of complex alloying compositions gives no possibility to distinguish the chemical groups of the metal and associate them with specific ore sources.